Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1017/s1047951112001795
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patent ductus arteriosus ligation in premature infants in the East of England: a prospective cohort study

Abstract: Patent ductus arteriosus ligation in premature infants is associated with low mortality and complication rates; however, there is a high incidence of neonatal morbidity. Surgical capacity for patent ductus arteriosus ligation needs to be carefully planned nationally as the duration of ‘‘waiting time’’ and transport to another surgical centre could adversely affect outcomes in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…There is a wide variation (0.7–67%) in the recorded incidence of LVCP post PDA ligation, as summarised in Table . The incidence (31%) of LVCP in the current study is comparable to that reported in the literature.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There is a wide variation (0.7–67%) in the recorded incidence of LVCP post PDA ligation, as summarised in Table . The incidence (31%) of LVCP in the current study is comparable to that reported in the literature.…”
Section: Discussionsupporting
confidence: 81%
“…There is a wide variation (0.7-67%) in the recorded incidence of LVCP post PDA ligation, as summarised in Table 4. 3,[7][8][9][10][11][12][13][14][23][24][25][26][27][28][29][30][31] The incidence (31%) of LVCP in the current study is comparable to that reported in the literature. Our study included infants less than 29 weeks gestation and the nasopharyngolaryngoscopy was done only if the infants were deemed symptomatic by the attending clinician.…”
Section: Discussionsupporting
confidence: 80%
“…Yet, the role of the RLN in respiration is more complex and less well understood[4]. While ample clinical [7, 42, 55] and basic [37] evidence document that RLN injury produces swallowing deficits, the exact mechanism of the performance problems remains elusive[34]. These results suggest that with detailed and fine-grained studies that include both respiration and swallowing have the potential to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the most frequent complication in the series was LPA stenosis (4.3% of cases), with no difference between PDA morphology or between patients greater or less than 5 kg. Compared to surgical ligation, the incidence of LPA stenosis is higher with device closure; however, complications such as pneumothorax, recurrent laryngeal nerve palsy, and chylothorax exist with surgical PDA ligation …”
Section: Discussionmentioning
confidence: 99%